Yayasan UMP extends help, prays Uqail immediately be found - Mimi Rabita, Abdul Wahit (2021)
KUANTAN, 4 January 2020 - Universiti Malaysia Pahang (UMP) was shocked by the news befalling the family of a student of the Faculty of Computing (FK), Uqail Iskandar Zulkernain, whose father, Zulkernain Itam, was drowned while trying to move household items due to flood.